Brain Penetrable Histone Deacetylase 6 Inhibitor SW-100 Ameliorates Memory and Learning Impairments in a Mouse Model of Fragile X Syndrome - Kozikowski, Alan P. (ACS Chem Neurosci, 2018)
Disease-modifying therapies are needed for Fragile X Syndrome (FXS), as at present there are no effective treatments or cures. Herein, we report on a tetrahydroquinoline-based selective histone deacetylase 6 (HDAC6) inhibitor SW-100, its pharmacological and ADMET properties, and its ability to improve upon memory performance in a mouse model of FXS, Fmr1(−/−) mice. This small molecule demonstrates good brain penetrance, low-nanomolar potency for the inhibition of HDAC6 (IC(50) = 2.3 nM), with at least a thousand-fold selectivity over all other class I, II, and IV HDAC isoforms. Moreover, through its inhibition of the α-tubulin deacetylase domain of HDAC6 (CD2), in cells SW-100 upregulates α-tubulin acetylation with no effect on histone acetylation and selectively restores the impaired acetylated α-tubulin levels in the hippocampus of Fmr1(−/−) mice. Lastly, SW-100 ameliorates several memory and learning impairments in Fmr1(−/−) mice, thus modeling the intellectual deficiencies associated with FXS, and hence providing a strong rationale for pursuing HDAC6-based therapies for the treatment of this rare disease.